Optimizing Collaborative Learning of Islamic Religious Education Through Social Media - Suriana Suriana; Teti Wahyuni; Misbahul Jannah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Digital native students increasingly require learning environments that are collaborative and digitally integrated. Islamic education (PAI) must adapt by leveraging social media to meet these demands. This study investigates how educators optimize collaborative PAI learning through the strategic use of social media platforms. This research employed a literature review methodology. Relevant academic articles were collected from databases including Google Scholar, SINTA, GARUDA, Connected Papers, Open Knowledge Maps, Semantic Scholar, and OhioLINK. Inclusion criteria focused on peer-reviewed studies published between 2018 and 2024 that discussed the use of social media to enhance collaborative PAI learning. Articles not directly related to the subject were excluded. The selected literature was categorized and analyzed using thematic content analysis. The findings reveal that educators are actively improving their social media literacy to facilitate collaborative learning. Three key efforts emerged: enhancing competence in digital platforms, integrating Islamic values into online interactions, and modeling appropriate social media behavior. These efforts contribute to creating dynamic, innovative, and student-centered learning environments. This review underscores the importance of educators maintaining up-to-date digital competencies to foster effective collaborative learning. The strategic use of social media not only enhances student engagement but also promotes the integration of religious values in modern learning contexts.